5(-2x+7)-3=52

Simple and best practice solution for 5(-2x+7)-3=52 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 5(-2x+7)-3=52 equation:



5(-2x+7)-3=52
We move all terms to the left:
5(-2x+7)-3-(52)=0
We add all the numbers together, and all the variables
5(-2x+7)-55=0
We multiply parentheses
-10x+35-55=0
We add all the numbers together, and all the variables
-10x-20=0
We move all terms containing x to the left, all other terms to the right
-10x=20
x=20/-10
x=-2

See similar equations:

| 21=-u+285 | | 214-y=160 | | 2x=3=2x+7 | | 0.25x8xx12=9x-6 | | -2(x-5)+4x=x-4 | | 9x7= | | 2m+4m=-18 | | X+2=-18+5x | | 3x–6=3–14x | | 18x+8+80=180 | | p=2.94(1.07)1999 | | 420+13x=25x | | -2x–6=6+10x | | 1/13(26x-169)=1/2(-156+24x) | | 8+2x=4–2x | | 50000+4x=14x | | 2x+8=4–2x | | 7n+50=120 | | 2^x-4x7^2x-10=196 | | 1/4x8xx12=9x-6 | | 2(u+7)=4u+22 | | 1/48x+12=9x-6 | | -4x+6=-2x–2 | | 45d+25=340 | | 4y+24=-9(y-7) | | -3(v-1)=-7v+39 | | 2x+3=9x-6 | | 4(x-6)=-2(1/2x-4) | | 50=-8w-6 | | 2x-9=-2–x | | F(x)=1/5x+4/15 | | t/60.2+1.5=5 |

Equations solver categories